2007
DOI: 10.1123/jab.23.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory versus Outdoor Cycling Conditions: Differences in Pedaling Biomechanics

Abstract: The aim of our study was to compare crank torque profile and perceived exertion between the Monark ergometer (818 E) and two outdoor cycling conditions: level ground and uphill road cycling. Seven male cyclists performed seven tests in seated position at different pedaling cadences: (a) in the laboratory at 60, 80, and 100 rpm; (b) on level terrain at 80 and 100 rpm; and (c) on uphill terrain (9.25% grade) at 60 and 80 rpm. The cyclists exercised for 1 min at their maximal aerobic power. The Monark ergometer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Namely, no bicycle motion (backward and forward displacements) was present in our study as would have been observed in real-life conditions. Moreover, exercising on a cycle ergometer does not allow real changes of the crank inertial load (Bertucci et al 2007;Hansen et al 2002). For example, Bertucci et al (2007) showed that at maximal aerobic power, the crank torque profiles during cycling on the ergometer were significantly different (especially on dead points of the crank cycle) and generate a higher perceived exertion compared to road cycling conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Namely, no bicycle motion (backward and forward displacements) was present in our study as would have been observed in real-life conditions. Moreover, exercising on a cycle ergometer does not allow real changes of the crank inertial load (Bertucci et al 2007;Hansen et al 2002). For example, Bertucci et al (2007) showed that at maximal aerobic power, the crank torque profiles during cycling on the ergometer were significantly different (especially on dead points of the crank cycle) and generate a higher perceived exertion compared to road cycling conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, exercising on a cycle ergometer does not allow real changes of the crank inertial load (Bertucci et al 2007;Hansen et al 2002). For example, Bertucci et al (2007) showed that at maximal aerobic power, the crank torque profiles during cycling on the ergometer were significantly different (especially on dead points of the crank cycle) and generate a higher perceived exertion compared to road cycling conditions. However, these facts, although important for generalization of the results, do not necessarily represent the drawback of our study, but quite the opposite.…”
Section: Discussionmentioning
confidence: 97%
“…However, good agreement between the Monark and SRM PO values has been reported [4,20] Not tested. Can be altered by the same things that alter the validity No (4) the preferred pedalling cadence [26], (5) the load pulse sum [27], (6) the gross efficiency [26], and (7) the rating of perceived exertion [22,25]. If ergometers with different inertia of flywheels are used for measurements, the results of experiments cannot be compared with good validity [27].…”
Section: Not Tested Yesmentioning
confidence: 96%
“…One of the most important factors is the inertial characteristics of the ergometer that can alter (1) the crank kinematics (e.g. cadence variability) [23,24], (2) the tangential crank force [24], (3) the crank torque [24,25], Lode (Excalibur Sport) [12,13] No mechanical validation, just tested from the comparison of the physiological data (oxygen consumption). No difference was found from 100 to 300 W…”
Section: Introductionmentioning
confidence: 99%
“…Using a conventional bicycle (outside of the laboratory) is a pleasurable of maintaining physical fitness. In their study, Bertucci et al [28] demonstrated that the muscular work of the lower limbs on a cycle ergometer does not significantly differ from the work on an outdoor bicycle. Therefore, in justified cases (under the supervision of a therapist), a stationary bicycle can be replaced with a bicycle for outdoor use that almost every person has.…”
Section: Discussionmentioning
confidence: 99%